Tale of a fish - Khan, Saniyasnain; Gurmeet (Goodword Kidz New Delhi, 2002)
Tale of a Fish by Khan Saniyasnain is a beautifully illustrated children$1 (Bs book that teaches valuable moral lessons through the story of a fish. The narrative follows the journey of a fish that learns about trust, patience, and the importance of following wise advice. Rooted in Islamic teachings, the story conveys themes of faith and guidance, showing how even the smallest creatures can impart important life lessons. Ideal for young readers, the book blends engaging storytelling with moral reflection, making it a thoughtful and inspiring read for children and families alike.s